Decolonizing Javanese-Islamic Identity in the Discourses of Contemporary Indonesian Islamic Studies - Mushthafa, M. Mushthafa (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This article discusses the phenomenon of decolonization of Islamic studies as a continuation of postcolonial critical projects that are widespread in various areas of study. In particular, this paper wants to answer two main questions: (1) the background and foundations of decolonization of Islamic studies and (2) its struggle in Indonesian Islamic discourse by focusing on the issue of Javanese-Islamic identity. By analyzing relevant data, this paper concludes that decolonization was motivated by scientists’ anxiety over the impact of colonialism in the academic-scientific area, which formed an oppressive cultural construction. Decolonization seeks to go beyond the postcolonial project, which, at a certain point, is still shadowed by the ideas of Western figures. The epistemological basis of decolonization is a critical approach in the study of religion in general, and it also involves political factors of knowledge in one of its dimensions. In Javanese-Islamic identity, decolonization emphasizes the close intertwining between Javaneseness and Islam, which tend to be separated in colonial studies.